Pemanfaatan Media Microlearning sebagai Solusi Inovatif Untuk Meningkatkan Pembelajaran Mahasiswa - Zohaib Hassan Sain; Deni Hartanto; Sirojul Fuadi (Insan Zenius Ilmiah, 2025)
The development of digital technology encourages higher education institutions to adopt more flexible, adaptive, and relevant learning strategies. Students as a digital generation need short, practical, and technology-based learning methods. One approach that is considered capable of answering these challenges is microlearning. Microlearning is a learning strategy that presents material in the form of small and dense units, which supports a fast and efficient learning process. Learning media plays an important role in optimizing this strategy, because it is able to convey content visually, auditorily, and interactively. The use of media such as short videos, animations, and infographics helps students understand concepts more easily and interestingly. This study aims to analyze the use of microlearning media as an innovative solution to improve the quality of student learning. In addition to exploring the form and effectiveness of the media used, this study also highlights various implementation challenges, such as limited technology infrastructure and digital literacy. The results of the study show that microlearning media is not only a learning aid, but also a driving force for the transformation of higher education. Therefore, a systematic implementation strategy and institutional support are needed so that microlearning media can be applied optimally and sustainably in the campus environment.